Temperature, Salinity and Dissolved Oxygen West and East seasons in the waters of Amurang Bay, North Sulawesi - Patty, Simon I.; Huwae, Rikardo (Sam Ratulangi University, 2023)
Observations of temperature, salinity, and dissolved oxygen have been carried out in Amurang Bay waters, North Sulawesi. This study aims to determine the temperature, salinity, and dissolved oxygen during the west and east seasonal monsoons. The statistical analysis results using the t-test showed that the temperature, salinity, and dissolved oxygen in the West monsoon with the east monsoon were significantly different. Temperature, salinity, and dissolved oxygen in the west monsoon are lower than in the east. Variations in temperature, salinity, and dissolved oxygen are influenced by atmospheric conditions, weather, rainfall, and current patterns. Implicitly, temperature and salinity can affect the solubility of oxygen in the East monsoon. The value of AOU (Apparent Oxygen Utilization) in the west monsoon is less than 0.00 mg/l (negative), which indicates that oxygen is very much needed for the process of respiration and decomposition of organic substances during the west monsoon. Keywords: oceanographic conditions, temperature, salinity, dissolved oxygen, Amurang Bay.